Characterization of a threonine-rich cluster in hepatitis C virus nonstructural protein 5A and its contribution to hyperphosphorylation - Schenk, Christian; Meyrath, Max; Schnölzer, Martina; Mier, Walter; Harak, Christian; Lohmann, Volker (Journal of virology, 2018)
Hepatitis C virus (HCV) nonstructural protein 5A (NS5A) is a phosphoprotein with key functions in regulating viral RNA replication and assembly. Two phosphoisoforms are discriminated by their different apparent molecular weights: a basally phosphorylated (p56) and a hyperphosphorylated (p58) variant. The precise mechanisms governing p58 synthesis and specific functions of the isoforms are poorly understood. Our study aimed at a deeper understanding of determinants involved in p58 synthesis. We analyzed two variants of p56 and p58 of isolate JFH-1 separately by mass spectrometry using an expression model and thereby identified a threonine-rich phosphopeptide exclusively found in the hyperphosphorylated variant. Individual exchange of possible phosphoacceptor sites to phosphoablatant or -mimetic residues had little impact on HCV replication or assembly in cell culture. A phosphospecific antibody recognizing pT242 revealed that this position was indeed phosphorylated only in p58 and depended on casein kinase Iα. Importantly, phosphoablative mutations at positions T244 and S247 abrogated pT242 detection without substantial effects on global p58 levels, whereas mutations in the preceding serine-rich cluster dramatically reduced total p58 levels but had minor impact on pT242 levels, suggesting the existence of distinct subspecies of hyperphosphorylated NS5A. Mass spectrometry analyses of different genotypes showed variable phosphorylation patterns across NS5A and suggested that the threonine-rich region is also phosphorylated at T242 in gt4a and at S249 in gt1a, gt1b, and gt4a. Our data therefore indicate that p58 is not a single homogenously phosphorylated protein species but rather a population of various phosphoisoforms, with high variability between genotypes. - IMPORTANCE Hepatitis C virus infections affect 71 million people worldwide and cause severe chronic liver disease. Recently, efficient antiviral therapies have been established, with inhibitors of nonstructural protein NS5A as a cornerstone. NS5A is a central regulator of HCV replication and assembly but is still enigmatic in its molecular functions. It exists in two phosphoisoforms, p56 and p58. We identified a phosphopeptide exclusively found in p58 and analyzed the determinants involved in phosphorylation of this region. We found evidence for very different phosphorylation patterns resulting in p58. These results challenge the concept of p58 being a homogenous species of NS5A molecules phosphorylated at the same positions and argues for at least two independently phosphorylated variants showing the same electrophoretic mobility, likely serving different functions.